2009
DOI: 10.1093/cercor/bhp184
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Facilitation at Mossy Fiber-CA3 Synapses of Freely Behaving Rats Contributes to the Induction of Persistent LTD via an Adenosine-A1 Receptor-Regulated Mechanism

Abstract: Frequency facilitation (FF), comprising a rapid and multiple-fold increase in the magnitude of evoked field potentials, is elicited by low-frequency stimulation (LFS) at mossy fiber–CA3 synapses. Here, we show that in freely behaving rats, FF reliably occurs in response to 1 and 2Hz but not in response to 0.25-, 0.3-, or 0.5-Hz LFS. Strikingly, prolonged (∼600 s) FF was tightly correlated to the induction of long-term depression (LTD) in freely moving animals. Although LFS at 2 Hz elicited unstable FF and unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 66 publications
1
28
0
Order By: Relevance
“…Thus, stimulation intensity during LFS was increased to evoke responses that reflect fEPSPs that comprise 70% of the maximum obtained in the input-output curve. LFS given at this intensity evokes persistent LTD in Sc-CA1 synapses (Manahan-Vaughan and Braunewell, 1999, 2005; Kemp and Manahan-Vaughan, 2004) and in mossy fiber- CA3 synapses(Hagena and Manahan-Vaughan, 2010). Interestingly, increasing the stimulation intensity during LFS resulted in synaptic potentiation (<3 h) at the pp-CA1 synapse in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, stimulation intensity during LFS was increased to evoke responses that reflect fEPSPs that comprise 70% of the maximum obtained in the input-output curve. LFS given at this intensity evokes persistent LTD in Sc-CA1 synapses (Manahan-Vaughan and Braunewell, 1999, 2005; Kemp and Manahan-Vaughan, 2004) and in mossy fiber- CA3 synapses(Hagena and Manahan-Vaughan, 2010). Interestingly, increasing the stimulation intensity during LFS resulted in synaptic potentiation (<3 h) at the pp-CA1 synapse in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In all hippocampal structures studied in our laboratory to date, low-frequency stimulation (LFS) consisting of 900 or 600 pulses at 1 Hz, has been shown to be effective in eliciting LTD and STD, respectively in Wistar rats (Manahan-Vaughan, 1997, 2000; Manahan-Vaughan and Braunewell, 1999; Kemp and Manahan-Vaughan, 2004; Poschel and Manahan-Vaughan, 2007; Hagena and Manahan-Vaughan, 2010). Therefore, this protocol was used to study synaptic depression at pp-CA1 synapses.…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…To avoid an influence on fEPSPs mediated by DCG-IV on subsequent experiments, it was ensured that potentials had fully recovered before those experiments were performed. In addition, routine studies were conducted to verify that NMDAR-dependent LTP was not evident in these synapses, as described previously (Hagena and Manahan-Vaughan, 2010). Here, 30 min before tetanisation to induce LTP, the NMDAR antagonist, D-(-)-2-amino-5-phosphonopentanoic acid (D-AP5) was applied to examine whether LTP was influenced by the antagonist.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of this form of LTP depends on presynaptic mechanisms (Staubli et al, 1990; Xiang et al, 1994; Weisskopf and Nicoll, 1995). Furthermore, LTD that is elicited by low-frequency stimulation (LFS), is preceded by potent facilitation of synaptic responses (called frequency facilitation) that is not seen at other hippocampal synapses (Salin et al, 1996; Toth et al, 2000; Moore et al, 2003; Hagena and Manahan-Vaughan, 2010). The role of mossy fiber (mf) plasticity in memory is unknown-however, the unique properties of frequency facilitation suggest it may play a role in working memory and/or informational integration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that application of the selective A1 receptor antagonist induced potent enhancement of mossy fiber response in vitro (Moore et al, 2003) and also in vivo (Klausnitzer and Manahan-Vaughan, 2008;Hagena and Manahan-Vaughan, 2010) by reducing tonic inhibitory effects of ambient adenosine. This effect is prominent at the mossy fiber synapse in comparison with adjacent associational-commissural synapse, and contributes, at least partly, to its characteristics such as low-release probability, large frequency facilitation and paired-pulse facilitation 4 (Nicoll and Schmitz, 2005).…”
mentioning
confidence: 99%